Nonverbal messages across cultures: Introducing nonverbal communication to university students - Stoian, Claudia (Technium Social Sciences Journal, 2020)
Nonverbal messages represent an important part of everyday communication. People are seldom aware of them, and thus disregard their individual and cultural variability, in other words, their potential for misunderstandings. The present paper aims to raise students’ awareness of the importance of nonverbal messages for a successful (intercultural) communicative event, and to introduce them to various nonverbal codes. For this, it proposes several activities focusing on nonverbal communication, in general, and on its different codes, in particular. These can be done in (foreign) language and communication classes to prepare students for real-life multicultural communicative events.